The relationship between quarter-life crisis and career anxiety among senior nursing students - Cahaya Sri Mega; Prastiwi Puji Rahayu; Slamet Riyanto (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Early adulthood (20–35 years) is a transitional phase full of developmental demands and prone to emotional stress in the form of a quarter-life crisis, characterized by confusion about life's direction, self-doubt, and anxiety about the future, particularly career anxiety. This phenomenon is often experienced by final-year students who are in the phase of determining their academic and career futures. Final-year students, as a group of early adults, are vulnerable to experiencing a quarter-life crisis, which results in increased career anxiety. Purpose: To determine the relationship between quarter-life crisis and career anxiety in final-year nursing students. Method: A descriptive correlation design, and the time approach used is cross-sectional. The analysis test uses the Spearman rank test. Results: The results of data analysis using the Spearman rank test obtained a correlation coefficient value of 0.538** with a significance of 0.000 ≤ 0.05, so Ha was accepted and Ho was rejected, which means there is a relationship between quarter-life crisis and career anxiety of final-year nursing students. Conclusion: Quarter life crisis affects career anxiety of final year nursing students. Keywords: Career Anxiety; College Students; Quarter Life Crisis.